Rational g-omega-weak contractions and fixed point theorems in 0-sigma-complete metric-like spaces - Nashine, Hemant Kumar Kumar; Gupta, Anita; Kadelburg, Zoran (Nonlinear Analysis: Modelling and Control, 2017)
We bring in the notion of rational g-ω-weak contractions in metric-like spaces and demonstrate common fixed point results for such mappings in 0-σ-complete metric-like spaces. Examples are given to support the usability of our results and to show that they are improvements of some known ones. An application to second-order differential equations is presented in the final section.